If God still breathes, why can't I? : Black Lives Matter and biblical authority - Parker, Angela N., 1971- (Grand Rapids, MI. W.B. Eerdmans Publishing Company, 2021)
"A challenge to the doctrine of biblical inerrancy and its role in propagating White supremacist authoritarianism in the Christian church"--
Stifled breathing: trained to be a white male biblical scholar -- White supremacist authoritarianism is not God's breath -- Stop gaslighting me -- Moving from stifled breath to full-throated faith.
Includes bibliographical references (pages 103-110) and index.
Keywords: Bible. -- Criticism, interpretation, etc; Bible -- Evidences, authority, etc; Race relations -- Biblical teaching; White supremacy movements -- Religious aspects -- Christianity; Authoritarianism -- Religious aspects -- Christianity; Black lives matter movement -- Religious aspects -- Christianity; Racism -- Religious aspects -- Christianity; Womanist theology; United States -- Race relations